Cracking the code of change in EU legal discourse: signifying practices shaping inclusion for vulnerable in the digital age - Notari, Fabiola (Comparative Legilinguistics, 2024)
The initiative of the Clear Writing Movement (Kimble 1992), targeting the democratization of communication by simplifying legal documents, has influenced the presentation of law globally. By uniting diverse philosophies of Plain Language and Easy-to-Read under the broad umbrella of text clarity and accessibility (Maaß 2020), this movement has particularly influenced the European Union’s linguistic policy (Foley 2002; Nerelius 2014; Seracini 2019). Notwithstanding this progress and the accelerated shift towards digital transformation during the Covid-19 pandemic, the European Union’s efforts to enhance its communication for vulnerable groups (European Union 2013) remains under-examined. This research, leveraging corpus linguistics and multimodal analysis, aims to systematically uncover foundational values and thematic clusters embedded in EU legal and policy documents related to the social inclusion and rights of vulnerable populations. It explores how these are dynamically communicated through easy-to-understand multimedia resources produced by Inclusion Europe and the European Commission (Bernabé 2020). Findings underscore the pivotal role of digital technology in revolutionizing the creation and interpretation of legal documents, reflecting the European Union’s proactive efforts to forge new avenues for multimodal legal communication marked by innovative signifying practices. The research concludes by emphasizing the socio-semiotic and context-specific dimensions of legal discourse. Far from being merely universal and abstract, it can be adapted and reshaped to reflect societal and political stances on regulated issues. This can foster a sense of belonging, empowerment, and inclusivity within vulnerable communities, while also nurturing broader societal cooperation and understanding.